Localization of components of the renin-angiotensin system in the suprachiasmatic nucleus of normotensive Sprague-Dawley rats: part A. Angiotensin I/II, a light and electron microscopic study - Thomas, Martin Alexander; Fleissner, Gerta; Stöhr, Marion; Hauptfleisch, Stefan; Lemmer, Björn (Brain research, 2004)
The central pacemaker of the mammalian circadian clock, identified in the suprachiasmatic nucleus (SCN), is of special interest for many chronomedical studies on neuropeptides. Based on its role in the modulation of blood pressure and vasopressin release, the distribution and function of the neuropeptide angiotensin II (ANG II) in the SCN became a target for several immunohistological studies. At the light microscopic level, the distribution of ANG II in the SCN is well known, but detailed information about the localization of ANG II in the SCN at the ultrastructural level is missing. To gain further insight in the functional aspects of ANG II in the SCN, we investigated on the subcellular localization of the neuropeptide ANG II and its precursor ANG I in the SCN. The current report presents a light and electron microscopic study on ANG I/II-immunoreactivity in the suprachiasmatic nucleus of normotensive Sprague-Dawley rats.